2009
DOI: 10.1074/mcp.m900124-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based Proteomics Profiling Reveals Increased Metabolic Activity and Cellular Cross-talk in Angiogenic Compared with Invasive Glioblastoma Phenotype

Abstract: Malignant gliomas (glioblastoma multiforme) have a poor prognosis with an average patient survival under current treatment regimens ranging between 12 and 14 months. The tumors are characterized by rapid cell growth, extensive neovascularization, and diffuse cellular infiltration of normal brain structures. We have developed a human glioblastoma xenograft model in nude rats that is characterized by a highly infiltrative non-angiogenic phenotype. Upon serial transplantation this phenotype will develop into a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 33 publications
3
65
0
2
Order By: Relevance
“…We have identified a number of annexins in our study to be overexpressed in GBM tumors including ANXA1 (log 2 ratio 3.91), ANXA2 (log 2 ratio 2.78), and ANXA5 (log 2 ratio 1.35). Previous studies have shown that ANXA2 and ANXA5 promote glioma cell invasion and tumor progression and are shown to be overexpressed in angiogenic compared with invasive GBM tumors (57,70). ANXA1, the annexin with the greatest magnitude of GBM overexpression in our study, has been found to be a major component in necrotic tumor cell-derived stimulants of the growth of GBM via the activation of formyl peptide receptor (FPR1) (69).…”
Section: Discussionmentioning
confidence: 74%
“…We have identified a number of annexins in our study to be overexpressed in GBM tumors including ANXA1 (log 2 ratio 3.91), ANXA2 (log 2 ratio 2.78), and ANXA5 (log 2 ratio 1.35). Previous studies have shown that ANXA2 and ANXA5 promote glioma cell invasion and tumor progression and are shown to be overexpressed in angiogenic compared with invasive GBM tumors (57,70). ANXA1, the annexin with the greatest magnitude of GBM overexpression in our study, has been found to be a major component in necrotic tumor cell-derived stimulants of the growth of GBM via the activation of formyl peptide receptor (FPR1) (69).…”
Section: Discussionmentioning
confidence: 74%
“…We have developed a clinically highly relevant human GBM model in rats that fully reflects the growth pattern of human tumors in situ, including extensive infiltration into the brain parenchyma (major pattern of invasion along fiber tracts and blood vessels), prominent angiogenesis, and necrosis (13)(14)(15). Comparative genomic hybridization studies have confirmed the genetic similarity between xenografted tumors and the corresponding human tumors (Fig.…”
mentioning
confidence: 83%
“…To visualize human tumor cells in the rat brain and to determine their distribution outside the tumor core, we used a human-specific nestin staining, a protein expressed by the vast majority of GBM cells (15,22,23). Interestingly, treated tumors revealed a more homogeneous morphology compared with the controls (Fig.…”
Section: Anti-vegf Treatment Reduces Vessel Density and Strongly Incrmentioning
confidence: 99%
“…Some earlier studies have focused on membrane proteome but using GBM cell lines and xenograft models (16,17). The aim of the current study was to build a high confidence, tumor-associated, differentially expressed membrane protein panel from clinical specimens of GBM, as a first step toward their targeted validation in a clinical setting by us and others in the community.…”
mentioning
confidence: 99%